2014
DOI: 10.4028/www.scientific.net/amm.575.507
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Underexpanded Co-Flow Jets

Abstract: The effect of inner nozzle lip thickness on the co-flow jet characteristics has been studied experimentally. Co-flow nozzles with inner nozzle lip thicknesses of 3 mm and 15 mm have been investigated. The thick-lip nozzle promotes mixing better than the thin-lip nozzle, for all the underexpanded operating conditions. The co-flow nozzle with thin-lip is effective in preserving the shock-cells nature, bringing down the longer shock-cell into shorter one and increasing the number of shock-cells compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Various authors (Kwan and Ko, 1977;Srinivasarao et al, 2014a;Matsumoto, 1973) studied incompressible flow coaxial jets. Kwan and Ko (1977) studied incompressible coaxial jets and observed that the PCL increases in the presence of an outer jet as observed in compressible jets (Papamoschou, 1997;Srinivasarao et al, 2017;Srinivasarao et al, 2014b;Lovaraju and Rathakrishnan, 2011;Perumal et al, 2020;Papamoschou, 1997). They also classified the regions of coaxial jets, namely, the initial merging zone (IMZ) (Region 1), intermediate zone (IZ) (Region 2) and fully merged zone (FMZ) (Region 3) as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 87%
“…Various authors (Kwan and Ko, 1977;Srinivasarao et al, 2014a;Matsumoto, 1973) studied incompressible flow coaxial jets. Kwan and Ko (1977) studied incompressible coaxial jets and observed that the PCL increases in the presence of an outer jet as observed in compressible jets (Papamoschou, 1997;Srinivasarao et al, 2017;Srinivasarao et al, 2014b;Lovaraju and Rathakrishnan, 2011;Perumal et al, 2020;Papamoschou, 1997). They also classified the regions of coaxial jets, namely, the initial merging zone (IMZ) (Region 1), intermediate zone (IZ) (Region 2) and fully merged zone (FMZ) (Region 3) as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 87%
“…CFJ from orifices with an annular gap 0.15 and 0.45 D p at Mach numbers 0.2, 0.4, 0.6, 0.8 and 1.0 and the corresponding NPRs 1.02, 1.12, 1.28, 1.52 and 1.89, respectively, were studied experimentally. The annular gap 0.45 D p found efficient mixing compared with 0.15 D p. (Srinivasarao et al (2014). CFJ with 3 mm LT (thin lip) (BR0.9) and 15 mm (thick lip) (BR0.5) at Mach number 0.6 and under-expanded (NPR 7) sonic jet, respectively, were studied experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the potential core length of the primary jet increases when the NPR increases for the coflow configuration compared to that without the coflow. Srinivasarao et al (2014), conducted experiments to study the effects of lip thickness to characterize underexpanded coflow jets of annular configuration (2014). The supersonic core length was found to be shorter as in the case of thick lip when compared with the jets from nozzles with a thin lip at different underexpanded cases of NPRs 3, 5 and 7.…”
Section: Introductionmentioning
confidence: 99%